Village cadre behavior in the household-based management of inorganic waste - Agnes Fitria Widiyanto; Arif Kurniawan; Elviera Gamelia (Masyarakat, Kebudayaan dan Politik, 2021)
Waste is still a problem in Indonesia. The increase in population causes the volume of waste to continue to grow, in Karangmangu Village, Banyumas Regency. Data on the increase in the volume of waste in Banyumas Regency reached 21.4%. The volume of inorganic waste is greater than organic waste because Karangmangu Village is a tourism buffer area in Baturraden. This study aimed to describe the knowledge, attitudes, and practices of cadres in the management of inorganic waste. The method used was descriptive qualitative. The research subjects were obtained using a purposive technique by conducting interviews with cadres as the main research subjects, midwives, and supporting informants. Data were collected through in-depth interviews and documentation. The results showed that the cadres had understood the definition, types, management, and negative impacts of inorganic waste. Based on their attitudes, the cadres consider the case of handling inorganic waste to be not optimal. In practice, they have sorted inorganic waste, managed a waste bank, made bricks, and produced handicrafts. Strategies to overcome obstacles in waste management are optimizing the facilities and infrastructure for the procurement of waste banks, as well as training more people to make handicrafts and market handicraft products. This study concludes that the presence of village cadres is able to increase public awareness in waste management.